Chicago monetary traditions - David Laidler (The University of Western Ontario, Department of Economics, 2003)
This paper, prepared for the forthcoming Elgar Companion to the Chicago School of Economics (Ross Emmett and Malcolm Rutherford eds.) describes monetary economics as it existed in four eras at the University of Chicago. It begins with analysis, based on the Real Bills Doctrine, developed by J. Laurence Laughlin, the first chairman of the Chicago Economics Department, and such students as Henry Parker Willis, which had an important influence on the original Federal Reserve Act, and then successively discusses: the inter-war Chicago tradition of such economists as Jacob Viner and Henry Simons, but also encompassing Paul Douglas's under-consumptionism; Milton Friedman's Monetarism; and New-classical economics as pioneered by Robert E. Lucas Jr. The paper's basic theme is that, although Chicago monetary thought has never been quite as unique and single-minded as some of its admirers have claimed from time to time, it did maintain a certain distinctiveness during its first three eras that has now disappeared.
Keywords: 330